Bio-inspired non self-similar hierarchical elastic metamaterials. (1st March 2023) - Mazzotti, M.; Foehr, A.; Bilal, O.R.; Bergamini, A.; Bosia, F.; Daraio, C.; Pugno, N.M.; Miniaci, M.
Abstract: Hierarchy provides unique opportunities for the design of advanced materials with superior properties that arise from architecture, rather than from constitutive material response. Contrary to the quasi-static regime, where the potential of hierarchy has been largely explored, its role in vibration mitigation and wave manipulation remains elusive. So far, the majority of the studies concerning hierarchical elastic metamaterials have proposed a self-similar repetition of a specific unit cell at multiple scale levels, leading to the activation of the same bandgap mechanism at different frequencies. On the contrary, here, we show that by designing non self-similar hierarchical geometries allows us to create periodic structures supporting multiple, highly attenuative and broadband bandgaps involving (independently or simultaneously) different scattering mechanisms, namely, Bragg scattering, local resonance and/or inertial amplification, at different frequencies. The type of band gap mechanism is identified and discussed by examining the vibrational mode shapes and the imaginary component of the wavenumber in the dispersion diagram of the unit cell. We also experimentally confirm this by performing measurements in the lowest frequency regime on a 3D printed structure. Hierarchical design strategies may find application in vibration mitigation for civil, aerospace and mechanical engineering. Graphical abstract: Highlights: A novel non self-similar hierarchical elastic metamaterial is proposed. Bragg, locally resonant and inertially amplified bandgaps are simultaneously activated. The multi-mechanism-based design leads to enriched dynamics at different scales.